Ajouts, omissions, substitutions : la main fautive des copistes dans le texte de L’Éducation sentimentale - Pierre-Marc de Biasi; Déborah Boltz (Flaubert: Revue Critique et Génétique)
“Finished! Old friend! Yes, this book of mine is finished … I have been at my table since yesterday, eight o’clock in the morning. My head’s about to burst. No matter, it's a real weight off my shoulders.” This is the famous note where Flaubert announces to Jules Duplan the completion of his novel that has taken him almost five years to write. But in fact, on May 16, 1869, Flaubert has not quite finished with his “bouquin”, as provesthe intense work of rereading and corrections that he will accomplish during the following months. After having spent a week “adjusting” his manuscript (from May 16th to the 24th), he hands it over to be copied. It is this carefully handwritten fair copy of the manuscript which the printer will use for his proofs. It is this same copy that Flaubert will send to a few close friends, in particular Maxime Du Camp who will write twelve pages of comments… Finally, it is also with this copy that Flaubert intends to correct “each phrase” of his text with Louis Bouilhet. But Bouilhet died prematurely at the end of July so it is on his own that Flaubert entered the final corrections to the Éducation Sentimentale. He spent about takes two weeks rereading and revising his manuscript which he then handed over to his publisher (August 14, 1869). The copyists’ copy – we have noted four different handwritings – has until today never been studied. Why? Probably because the act itself of “copying” has always been considered negligible, quite insignificant. It is thought that the copyist’s manuscript is incapable of revealing anything of interest since it is only the slavish reproduction of the definitive autograph Manuscript… In fact this is not the case at all. This manuscript constitutes an irreplaceable genetic document, all the more essential that we do not have access to the corrected proofs of the novel. Aside from the last minute changes decided by Flaubert himself, this copy contains numerous mistakes due to the copyists’ negligence. These alterations of the text escaped Flaubert’s notice and were subsequently reproduced in two editions of the Éducation sentimentale published during his lifetime (1869 and 1879). We will try to show with precise examples how these errors – of all kinds (additions, omissions, substitutions, displacements…) – have in many ways modified the very reading of the text of the Éducation sentimentale. What repercussions have these modifications, not willed by the author himself, on the meaning or the interpretation of the novel? What are the networks of meaning not desired by the author that have been abusively induced by these “misreadings”? Vice versa, what are the significant logics built by the author that we are deprived of because of these slips of the pen?